Can commodities be substances of value? - Deepankar Basu (University of Massachusetts, Department of Economics, 2020)
The Marxian labour theory of value considers labour as the only substance of value. The generalized commodity exploitation theorem (GCET) purports to demonstrate that many other commodities can be substances of value. This note argues that the GCET is based on two conceptual aws: (a) failure to distinguish labour and labour-power; and (b) failure to distinguish labour-power and other commodities. Once these aws are corrected, it is easy to show that commodities cannot function as the substances of value. Only labour can be the substance of value.
Keywords: B51; 330; labour theory of value; generalized commodity exploitation theorem